RNF6 activates TGF-β1/c-Myb pathway to promote EMT in esophageal squamous cell carcinoma - Cheng, Jingge; Wu, Kun; Yang, Qian; Zhu, Ziming; Zhao, Hongye (Frontiers in Oncology, 2023)
Objective: This study aimed to investigate RING-Finger Protein 6 (RNF6) expression in esophageal squamous cell carcinoma (ESCC) cells and whether it affects cell proliferation, invasion, and migration by regulating the TGF-β1/c-Myb pathway. Methods: TCGA database was used to analyze RNF6 expression in normal tissues and esophageal cancer tissues. Kaplan–Meier method was used to examine the correlation between RNF6 expression and patient prognosis. SiRNA interference vector and RNF6 overexpression plasmid were constructed, and RNF6 was transfected into Eca-109 and KYSE-150 esophageal cancer cell line. In vitro scratch assay and Transwell assay were conducted to investigate the effects of RNF6 on the migration and invasion of Eca-109 and KYSE-150 cells. RT-PCR detected the expression of Snail, E-cadherin, and N-cadherin, and TUNEL detected the apoptosis of cells. Results: RNF6 up-regulation promoted the progression of esophageal cancer and predicted poor prognosis. RNF6 also enhanced the migration and invasion of ESCC cells in vitro. RNF6 silencing inhibited the migration and invasion of ESCC cells. TGF-β inhibitors reversed the oncogenic effects of RNF6. RNF6 regulated the migration and invasion of ESCC cells by activating the TGF-β pathway. RNF6/TGF-β1 promoted esophageal cancer progression through c-Myb. Conclusion: RNF6 promotes the proliferation, invasion, and migration of ESCC cells possibly by activating the TGF-β1/c-Myb pathway and affects the progression of ESCC.